Rapid vision improvement by using icotinib in a patient with bilateral choroidal metastases symmetrically from lung cancer - Chaoran Li; Xue E Wang; Lei Yan; Yani Zhao; Yun Kui Zhu (The Clinical Respiratory Journal, 2023)
Abstract Introduction The metastases of lung cancer to bilateral choroids symmetrically and simultaneously are very rare. Almost all patients with choroid metastasis can be treated with external beam radiotherapy in order to increase quality of life and preserve vision. Material and Methods We documented a case and studied the effect of icotinib on choroidal metastases in bilateral eyes simultaneously from pulmonary adenocarcinoma. Results A 49‐year‐old Chinese man presented with bilateral vision losing simultaneously for 4 weeks, it was as an initial presentation in the clinical. The examinations with ophthalmofundoscopy, ultrasonography, and fluorescein angiography showed the lesions in bilateral choroids, two solitary juxtapapillary yellow‐white choroidal metastases inferior to the optic discs with bleeding. Positron emission tomography confirmed the choroidal metastases and further proved that it was from lung cancer with lymph nodes and multiple bone metastasis. The biopsy taken from the lung by bronchoscopy and needle biopsy from supraclavicular lymph nodes revealed the pulmonary adenocarcinoma with epithelial growth factor receptor mutation (exon 21). The patient was treated with oral icotinib (125 mg, three times a day, TID). Five days after starting icotinib therapy, the patient's visions were rapidly recovered. Two months after the treatment with icotinib, the choroidal metastases regressed to small lesions, and the visions were preserved to before. The lung tumor and other metastatic lesions were partly regressive. There was no evidence of recurrence for eye lesions at 15‐months follow‐up. After 17 months treating by icotinib, the patient presented headache and dizzy with multiple brain metastases determined by magnetic resonance imaging; however, the lesions of the choroidal metastases remained progressing‐free. Almonertinib with radiotherapy were used to treat the brain metastases, and he is surviving with progress‐free more than 2 years until now. Conclusion Bilateral choroidal metastases from lung cancer symmetrically are very rare. Icotinib following by almonertinib was an alternative therapy for choroidal metastasis from non‐small cell lung cancer with epithelial growth factor receptor mutation.